Analisis Variabel yang Memengaruhi Harga Properti Residensial Tipe Kecil di 16 Kota Indonesia Tahun 2015-2019 - Aisyah Bintang; Neli Agustina (Seminar Nasional Official Statistics, 2021)
Private residence is a basic need that must be fulfilled. The housing development policy in the 2015-2019 RPJMN is aimed at increasing public access (especially low-income communities) for decent housing. However, the high price of residential property has a big impact for low-income communities. Therefore, this study will examine the determinants of small-type residential property prices in 16 Indonesian cities 2015-2019. The analytical method used in this research is panel data regression analysis with SUR. The results showed that the variable monthly wages of construction workers and regional GDP were positively affecting small-type RPPI. Meanwhile, the regional GDP share’s of construction, the realization of FLPP, and unemployment rate have a significant negative effect on small type residential property index. Through this research, the government is expected to provide the right policy so that the needs of residential property for low income communities can be fulfilled.